Raw water challenges: difficulties and alternatives for municipal treatment - Hernández Cortes, Andrea; Saby Beltrán, Jorge Enrique (Ingeniería Solidaria, 2025)
Introduction: The current state of wastewater treatment presents various challenges worldwide. In Colombia, municipal WWTPs face technical and operational limitations. This article is the result of research on the wastewater treatment system of Barichara, conducted at Universidad Francisco José de Caldas in 2025. Problem: Currently, only about 10% of Colombian WWTPs comply with the parameters established for the discharge of treated wastewater into water sources, a worrying figure that alerts municipalities such as Barichara, where the plant is inoperative. Objective: The research aims to identify the main difficulties in implementing municipal WWTPs in Colombia, using Barichara as a case study. It seeks to determine common factors that may affect similar systems across the country. Results: Implementing these systems requires not only proper structural design but also a solid understanding of biological and chemical processes. Inefficiencies often arise from the lack of integration between design and local environmental or technical conditions. Conclusions: One of the main problems is the selection of inappropriate treatment units that do not align with the specific characteristics of each municipality. Thus, the lack of synergy between structural and environmental design in the selection of treatment units is critical. Originality: The research contributes by proposing adaptable, efficient, and sustainable alternatives that can be applied to small municipalities facing similar challenges. Limitations: The analysis is based on a single case, which limits the direct generalization of the findings to other plants in the country.